MISCELLANEOUS BOTANICAL NOTES-IV* - C. G. G. J. VAN STEENIS (Research Center for Biology, 1952)
1. In connection with the first record from Malaysia (Atjeh, North Sumatra)of a species of Schoepfia (Olacaceae), viz. S. fragrans Wall, in Roxb., some notes on the genus are given, including a key to the species of section Schoepfiopsis (emended) and to the two Indian species of Schoepfia.The specimens of the Kew and Leyden Herbaria of these two species are listed. The name Schoepfia ffriffithii Tiegh. is validly published in the present paper, if this was not done before. 2. Smilax pygmaea Merr. (Liliaceae) is recorded from Atjeh, Sumatra. 3. The first indigenous species of Mivmlus (Scrophulariaceae), M. tenellus Bunge,is recorded for Malaysia from Atjeh, Sumatra. 4. A new species of Macadamia (Proteaceae) is described from Celebes: Macadamia hildebrandii Van Steenis. It belongs to the same genus as the common Australian bush nut, M. ternifolia, with edible seeds. 5. Some information, additional to a previous paper on Biophytum (Oxalidaceae)in Malaysia, is given. 6. Some records of plants new to Mount Pangrango, West Java, are mentioned. 7. The recent introduction and the present distribution in Malaysia of the weed Eupatorium odoratum L. (Compositae) is discussed. 8. Some additional records of the liana Hollrungia aurantioides K. Schum.(Passifloraceae) from New Guinea and from outside this island (Ternate, Moluccas)are published.